Caffeine and beetroot juice optimize 1,000-m performance: Shapley additive explanations analysis - Liu, Xiao; Huo, Lei; Wang, Feng; Wang, Tian; Rong, Wenchao; He, Yu (SAGE Publications, 2025)
The 1,000-m run is a key component of university physical fitness assessments. Effective supplementation strategies to enhance performance and recovery in this test remain underexplored. This study aimed to evaluate the effects of caffeine (CAF) and beetroot juice (BJ) on 1,000-m performance and used SHapley Additive exPlanations (SHAP) analysis to identify key influencing factors. A randomized crossover design compared the effects of CAF (6 mg/kg body weight), BJ (70 mL providing 6.4 mmol of (Formula presented.) ), and their combination with placebo (PLA) on 1,000-m running performance. Twenty healthy male participants took part in the study. Physiological, nutritional, and behavioral data were collected during each condition. SHAP analysis of a multilayer perceptron model quantified the relative importance of various performance determinants, providing a clear assessment of their contribution to the outcome. The CAF + BJ group performed significantly better than PLA (p <.01) in the first 1,000-m run and outperformed both PLA and BJ in the second run (p <.01). Performance declined after recovery in BJ (p <.01) and PLA (p <.01) but improved in CAF + BJ (p <.01). Post-exercise heart rate and blood lactate were highest in CAF + BJ and CAF, with CAF showing significantly higher lactate levels at 10, 15, and 20 min post-exercise compared to CAF + BJ (p <.01). SHAP analysis ranked body fat percentage > weight > age > nighttime sleep duration > nutritional strategy > average vertical jump height > grip strength > resting heart rate > time since last meal > alcohol consumption > height > smoking frequency. This study suggests that CAF and BJ supplementation may improve 1,000-m performance. SHAP analysis introduced a novel framework for identifying key factors, offering insights for targeted interventions. Tailored dietary supplement strategies that address critical physiological and lifestyle factors are important. Combining supplementation with these approaches can further enhance performance and recovery.